CIVIL LIABILITY OF OPEN COMPANIES THAT PARTICIPATE IN TAX AMNESTY PROGRAM AGAINST THE INVESTORS - Junaidi, Anang Saifudin; Moersidin, Murry Darmoko (jfpublisher, 2022)
The number of online financial service platforms in Indonesia is increasing every year. However, many illegal platforms operate without registration under the Financial Services Authority. This rise is driven by several factors, including the ease of creating online loan service applications, uneven access to bank financing, and the rapid acceleration of digitalization—particularly in online loan platforms—without adequate public knowledge and literacy. Additionally, the administration of online loan services is often too easily accessible. Law enforcement and dispute resolution for illegal online financial services have yet to fully uphold the principles of legal protection and fairness for borrowers registered under Financial Services Authority regulations.